2012
DOI: 10.1097/mao.0b013e318268d52d
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Abilities After Cochlear Implantation in Adults With Unilateral Deafness

Abstract: Objective This pilot study examined speech recognition, localization, temporal and spectral discrimination and subjective reports of cochlear implant (CI) recipients with unilateral deafness. Study Design Three adult males with short-term unilateral deafness (< 5 years) participated. All had sudden onset of severe to profound hearing loss in one ear, which then received a CI, and normal or near normal hearing in the other ear. Speech recognition in quiet and noise, localization, discrimination of temporal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
124
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 24 publications
16
124
1
Order By: Relevance
“…Both auditory brainstem response and EEG studies on sequentially implanted children confirmed such an effect with objective measures [Sharma et al, 2005;Gordon et al, 2011Gordon et al, , 2013. Similarly with respect to localisation performance, early single-sided deafness after cochlear implantation shows a smaller benefit compared to postlingual onset [Firszt et al, 2012b].…”
mentioning
confidence: 70%
“…Both auditory brainstem response and EEG studies on sequentially implanted children confirmed such an effect with objective measures [Sharma et al, 2005;Gordon et al, 2011Gordon et al, , 2013. Similarly with respect to localisation performance, early single-sided deafness after cochlear implantation shows a smaller benefit compared to postlingual onset [Firszt et al, 2012b].…”
mentioning
confidence: 70%
“…In SSD adults, several studies demonstrated improvements in qualities supporting higher-level processing and integration of both acoustic and electrical signals leading to improved overall hearing. The improvements in performance reported for younger CI patients with acquired SSD suggest that results were equivalent to those seen for SSD adults and show evidence of rehabilitation of binaural hearing and similar improvement in the quality of speech comprehension in noise and the ability for sound localisation [Arndt et al, 2011a, b;Punte et al, 2011;Stelzig et al, 2011;Firszt et al, 2012;Plontke et al, 2013].…”
mentioning
confidence: 99%
“…Despite this increase in cochlear function of the SSD ear, the binaural benefits of free-field speech comprehension gleaned after implantation are limited in quiet environments, likely because the normal hearing ear doesn't need to rely on binaural squelch and summation when noise is not present. In a case series with 3 subjects implanted for SSD, Firszt et al reported only 1 patient who showed statistically significant improvements in CNC speech scores in the bimodal, quiet condition compared to either unilateral NH or CI-alone conditions [8]. In the same study, adding noise to the speech tests resulted in 2/3 patients showing significantly better CNC scores in the bilateral condition than solely with either the normal hearing ear alone.…”
Section: Speech Benefits After Unilateral Cochlear Implantationmentioning
confidence: 71%
“…Additionally, patients with CIs performed significantly better with their CI when localizing than in unaided, CROS, and Baha conditions [10]. In a case series of 3 patients, Firszt et al demonstrated improvements in localization in 10°i ncrements when sound was presented to the CI ear, NH ear, and bilaterally [8].…”
Section: Sound Localization Benefits After Unilateral Cochlear Implanmentioning
confidence: 99%
See 1 more Smart Citation